O Contestado nas narrativas militares : histórias e memórias sobre o movimento social, 1912-1916 - Figueiredo, Vagner Melo (2016)
The Contestado War was an armed conflict occurred between the years 1912 and 1916 in southern Brazil, where the Brazilian government acted to quell a movement that claimed social rights. Beyond the mystical content, this uprising came under social, political and economic pressure. The objective of this research is to understand the construction of memories on the movement and on those workers who were willing to take up arms to defend their rights in a society engaged in experimenting the change of their way of life, imposed by capitalist practices implemented by the newly created Brazilian Republic. The State acted in the repression of the movement employing troops that, during the campaign, lived with the backlanders against which fought, providing those military the opportunity to testify about the culture of those subject, as did the authors of the military documents from the war, works memoir about the military campaign and magazine articles specialized in military affairs. The authors of these sources recorded the events and his impressions from your social site, building memories about the movement and its subjects. How did the production of Contestado from these narratives? What were your senses and interests in the construction of memories on Contestado?